2007
DOI: 10.1093/hmg/ddm301
|View full text |Cite
|
Sign up to set email alerts
|

HYPK, a Huntingtin interacting protein, reduces aggregates and apoptosis induced by N-terminal Huntingtin with 40 glutamines in Neuro2a cells and exhibits chaperone-like activity

Abstract: Expansion of polymorphic glutamine (Q) numbers present at the protein Huntingtin (Htt) beyond 36Q results in its misfolding and aggregation, and the aggregates recruit several other proteins. Here we show that HYPK, initially identified as an Htt-interacting partner by yeast two-hybrid assay, physically interacts with N-terminal Htt in Neuro2A cells and alters the numbers and distribution of aggregates formed by N-terminal Htt with 40Q. HYPK also alters the kinetics of mutated N-terminal Htt-mediated aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 43 publications
3
69
0
Order By: Relevance
“…be enriched for intrinsically disordered (naturally unfolded) proteins, since intrinsically disordered proteins are involved in several kinds of diseases, especially neurodegenerative diseases, including HD. 26,27,33 We found that 76% of 50 randomly selected preferential interactors of Htt-50Q contain regions of disorder of ≥ 30 residues, as predicted by at least three out of four PONDR predictors used, compared with 47% in the total pool of eukaryotic proteins in SwissProt database. 27 To identify proteins most significantly changed in abundance between normal and expanded Htt complexes, we used statistical analysis of variance (ANOVA) approach, which considers both biologic and experimental sources of variability.…”
Section: Resultsmentioning
confidence: 88%
“…be enriched for intrinsically disordered (naturally unfolded) proteins, since intrinsically disordered proteins are involved in several kinds of diseases, especially neurodegenerative diseases, including HD. 26,27,33 We found that 76% of 50 randomly selected preferential interactors of Htt-50Q contain regions of disorder of ≥ 30 residues, as predicted by at least three out of four PONDR predictors used, compared with 47% in the total pool of eukaryotic proteins in SwissProt database. 27 To identify proteins most significantly changed in abundance between normal and expanded Htt complexes, we used statistical analysis of variance (ANOVA) approach, which considers both biologic and experimental sources of variability.…”
Section: Resultsmentioning
confidence: 88%
“…Expression of fluorescent-tagged mutated exon1 of HTT (mHTT) in cultured cells led to the formation of m-HTT aggregates as described by many authors including us. 25,26 To study the effect of miRNAs on aggregate forming propensity of the m-HTT, we engineered HTT exon1. We ligated HTT exon-1 (that codes 83 Glu for mutated HTT and 16 Glu for wild-type HTT) with the full length 3'-UTR of mouse Htt gene.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Here we present data identifying the Huntingtin (Htt) yeast two-hybrid protein K (HYPK) as a novel factor involved in cotranslational NatA acetylation. HYPK, originally identified in a yeast two-hybrid screen during a search for potential interaction partners for the Huntingtin protein (19), was recently found to reduce Htt polyglutamine (polyQ) aggregation upon overexpression (36). However, the role of the endogenous HYPK protein has yet to be revealed.…”
mentioning
confidence: 99%